2019
DOI: 10.19184/issrd.v1i1.13726
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Traditional Market Revitalization on the Traders’ Capital Expenditures in Situbondo

Abstract: The impact of traditional market revitalization has an effect on the expenses and business capital of traders. Traditional markets are the economic fulcrum of the community, but traditional market conditions are synonymous with slums, dirty, smelly, irregular, muddy and so on. To survive the onslaught of modern markets there needs to be a revitalization of traditional markets, the emphasis is on the physical aspects of the market. so the hope of traders is that consumers interested in shopping in the market an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…It was also reported that most of the revitalisation budget was spent on the physical repair. However, previous research showed that some of the revitalisation process was not beneficial to all the stakeholders (Fauzi and Firadaus 2018;Fatmawati and Lantu 2017).…”
Section: Resultsmentioning
confidence: 96%
“…It was also reported that most of the revitalisation budget was spent on the physical repair. However, previous research showed that some of the revitalisation process was not beneficial to all the stakeholders (Fauzi and Firadaus 2018;Fatmawati and Lantu 2017).…”
Section: Resultsmentioning
confidence: 96%
“…Pedagang memiliki membangun kiosnya sendiri kemudian menutup dan membereskannya ketika telah selesai menjual. (Fauzi et al, 2018) Kios yang dibangun sendiri oleh pedagang ini mengakibatkan kawasan pasar terlihat tidak bersih, tidak tertib, dan tidak teratur. Pedagang yang tidak ingin membangun kios juga menggunakan mobil untuk menjajakan barang dagangannya.…”
Section: Pendahuluanunclassified
“…Di lokasi pasar yang baru pedagang masih menggunakan lapak semi permanen dengan menggunakan bambu atau kayu. Kondisi lapak pedagang di pasar baru yang lebih sempit dan terbuat dari bambu atau kayu tersebut menjadi salah satu masalah dalam relokasi pasar sesuai dengan hasil penelitian 92,30% (Fauzi and Firdaus, 2019) yang menyatakan bahwa bangunan pasar baru tidak sesuai dengan ekspektasi pedagang sehingga menimbulkan protes dari pedagang pasar. Di pasar baru lokasinya kurang tertata dengan baik sesuai zona seperti di pasar lama, sehingga pedagang kehilangan pelanggan tetapnya.…”
Section: Metode Penelitianunclassified